A comparative study of microstructure and magnetic properties of a NiFe cemented carbide: Influence of carbon content. (April 2019) - Linder, David; Hou, Ziyong; Xie, Ruiwen; Hedström, Peter; Ström, Valter; Holmström, Erik; Borgenstam, Annika
Abstract: Due to the renewed interest in alternative binders for cemented carbides it is important to understand how the binder composition influences not only mechanical properties but also the microstructure and related measurements for quality control. Microstructure and chemical composition of WC-Co is often evaluated by magnetic measurements. However, when the binder composition deviates significantly from conventional Co-based binders it should not be assumed that the standard measurements can be used to directly evaluate the same parameters. In this paper we investigate the influence of relative C-content on the microstructure and magnetic properties of an alternative binder cemented carbide. It is shown that the saturation magnetization is related to the relative C-content and the magnetic coercivity is related to the microstructure, more specifically to the binder phase distribution, but could not be directly linked to the carbide grain size in the same manner as for standard WC-Co. Furthermore, a direct correlation between Curie temperature and saturation magnetization is observed for this system which means that the Curie temperature potentially could be used for calibration of empirical relations or as a method to accurately determine the binder volume fraction. Highlights: Cemented carbides with a NiFe alternative binder were produced and characterized. Increasing C-content gives larger grain size and homogeneous binder distribution. Magnetic properties are sensitive to the binder composition and the microstructure. Empirical models for magnetic quality control of WC-Co are not directly useable. Curie temperature is shown to be a useful complement for calibration of the models.